Correlation Among Psychological Resilience, Social Support, and Coping Style in Patients With Complicated Hepatolithiasis - Wang, Ying; Huang, Chunqiu; Zhang, Honghui; Cai, Yimin; Shen, Zhoumin; Hu, Xiahong; Zhou, Bifang; Yang, Lifen; Chen, Qian (Frontiers in Behavioral Neuroscience, 2022)
Objectives: To investigate the correlation between psychological resilience, social support, and coping styles in patients with complicated hepatolithiasis. Methods: The objective sampling method was used in this study to select a total of 156 patients with complicated hepatolithiasis in a Third-class Grade A hospital in Changsha, Hunan Province from January to December 2019. Self-designed general data questionnaire, the Connor-Davidson Resilience Scale (CD-RISC), the Social Support Rating Scale (SSRS), and the Simplified Coping Style Questionnaire (SCSQ) were used to conduct a questionnaire investigation. Spearman correlation analysis was used to analyze the correlation between psychological resilience, social support, and coping styles in patients with complicated hepatolithiasis. Results: Both the total score of psychological resilience (45.79 ± 16.28) and social support (35.71 ± 9.92) of patients with complicated hepatolithiasis were significantly lower than those of the domestic norm. The total score of psychological resilience of patients with complicated hepatolithiasis was positively correlated with the total score of social support (r = 0.570, p < 0.01). The total score of psychological resilience and its three dimensions were positively correlated with the positive coping (r = 0.682, 0.673, 0.663, 0.535, p < 0.01)and negatively correlated with negative coping (r = −0.240, −0.207, −0.221, −0.286, p < 0.01). Conclusions: This study indicated that strengthening social support and improving the coping style of patients with complicated hepatolithiasis are helpful to improve their psychological resilience, which provided theory basis and reference for further intervention measures to improve social support system and coping styles.